2011
DOI: 10.1186/1471-2296-12-122
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of undiagnosed chronic obstructive pulmonary disease in a primary care population with respiratory tract infections - a case finding study

Abstract: BackgroundChronic obstructive pulmonary disease (COPD) is an underdiagnosed cause of morbidity and mortality worldwide. Prevalence of COPD has been shown to be highly associated with positive smoking history and increasing age. Spirometry is the method used for diagnosing COPD. However, identifying patients at risk of COPD to undergo spirometry tests has been challenging. Therefore, there is a need for new cost-effective and feasible diagnostic screening procedures for use in primary care centers. Our aim was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
39
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 38 publications
4
39
2
Order By: Relevance
“…Our study showed that older age and increased pack years smoking are the main factors associated with COPD development. Approximately 1 in 10 patients aged < 55 years and 1 in 4 patients aged 55 years or older had COPD, and 22.4% of those with pack years smoking > 30 develop COPD compared with 7.2% of those with pack years ≤ 30, This is comparable to the findings of other studies (19,(22)(23)(24). Chronic inhaled cigarette smoke leads to chronic lung inflammatory response, which induces parenchymal tissue destruction and disrupts the normal repair mechanism leading to airway fibrosis and narrowing and a decrease in FEV1 (3).…”
Section: Discussionsupporting
confidence: 87%
“…Our study showed that older age and increased pack years smoking are the main factors associated with COPD development. Approximately 1 in 10 patients aged < 55 years and 1 in 4 patients aged 55 years or older had COPD, and 22.4% of those with pack years smoking > 30 develop COPD compared with 7.2% of those with pack years ≤ 30, This is comparable to the findings of other studies (19,(22)(23)(24). Chronic inhaled cigarette smoke leads to chronic lung inflammatory response, which induces parenchymal tissue destruction and disrupts the normal repair mechanism leading to airway fibrosis and narrowing and a decrease in FEV1 (3).…”
Section: Discussionsupporting
confidence: 87%
“…Milenkovic et al reported a similar prevalence of chronic bronchitis in Belgrade area (21.6%) [15]. In a Swedish study of the patients with an acute respiratory infection, treated in the primary care, COPD was diagnosed in 27% of the cases [16]. Of particular importance is the fact that most COPD cases are diagnosed in stages III and IV of the disease, when the respiratory reserve is already reduced by over 50%, while the greatest reduction of lung function parameters occurs in the disease stages I and II [17].…”
Section: Discussionmentioning
confidence: 70%
“…Rudolf et al report that almost 75% of COPD patients in West Europe do not have the adequate diagnosis and treatment [10], most of them in the GOLD stages I and II [16]. Sandelowsky et al have reported that middle-and old-aged smokers with acute respiratory infection, treated in the primary care, often have an undiagnosed COPD; therefore, the authors suggest to control spirometry parameters in these patients four weeks after the treatment is discontinued [16]. COPD and asthma often fail to be recognized and diagnosed in the patients over 50 with a chronic cough [19].…”
Section: Discussionmentioning
confidence: 99%
“…A parameter with no discriminative value would have the area under the ROC curve approximately higher than 0.5 and lower than 0.6. Area between 0.6 and 0.7 indicates "poor" performance, area between 0.7 and 0.8 "fair" performance, and area between 0.8 and 0.9 "good" performance [16,17]. Parameters belonging to the category "excellent" usually have the ROC areas higher than 0.9.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphoma microenvironment includes fibroblasts, follicular dendritic cells, mesenchymal stromal cells, antigen-presenting cells, and immune cells, such as macrophages, T-and B-cells, and mast cells. Table 1 Area under the ROC curve for the parameters showing any discriminative power between mast cell patterns in lymphoma and mastocytosis, and classification of their accuracy [14,15] (Zweig and Campbell [16], Sandelowsky [17]) as binary classifiers.…”
Section: Discussionmentioning
confidence: 99%